THE SUPERVISION EFFECTIVENESS ON THE IMPLEMENTATION OF ENVIRONMENTAL PERMIT OF SPLIT STONE AND SAND MINING IN THE PALU CITY - Insarullah, Insarullah (Tadulako University, 2020)
Natural resources management in mining has to be managed with environmental oriented policies. The mining split stone and sand mining business in Palu City, especially in the two kelurahan (Buluri and Watusampu) has caused environmental damage that has an impact on the lives of people in the area. This research uses socio-legal research method, research population come from the community around the mining region of split stone and sand in Palu. The sample selected randomly, there are 20 people from the two aforementioned kelurahan which became the research location in Palu. Both of the kelurahan is the center of split stone and sand mining business by the mining company. The mining site located in the fringing road area of Sulawesi main route from Palu to Donggala. Result of the research indicates that the control to environmental permit implementation at the split stone and sand mining in the Palu City is not effective. It is shown from the environmental impact that happened alongside the axis road between Palu and Donggala. There are visible environmental damage and health problem for the resident of the two kelurahan. The tenuous supervision influenced by some factor, namely: the human resource of supervising staff; allocation of control fund; and control supporting facility.